DEVELOPING A TEACHING MODEL OF BASIC MOVEMENT FOR KIDS AT 2 TO 4 YEARS OLD - Bambang Prayitno (Universitas Muhammadiyah Purwokerto, 2014)
The aim of this study was to develop a teaching model of basic movement for children of 2 to 4 years old. The teaching model was based on their development aspect and characteristics and it was focused on three basic movements: locomotors, non locomotors, and manipulative movements. This is a research and developmental study. The development of the teaching model was conducted in seven steps: 1) collecting information; 2) information analysis; 3) developing initial product; 4) expert`s validation and revision; 5) preliminary field test and revision; 6) main field test and revision; and 7) making the final product. The subject of this research was 2 to 4 year old children. The result of this study is in the form of a manual for basic movement teaching for two to-four-year-old children, that consists of seven teaching models: 1) Creeping and Crawling; 2) Walking on the Rope; 3) Throwing Bean Bag to the Hula-Hoop; 4) Bowling Games; 5) Parachute Games; 6) Climbing; and 7) Jumping. As a conclusion, the teaching model is very good and effective. From the evaluation of experts and teachers, it can be concluded that the developed model is very good and appropriate with the characteristic, growth, and development of two-to-four-year-old children`s movement